Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

Cerebral vasculopathy in a Chinese family with neurofibromatosis type I mutation - Jian-Tao Liang; Li-Rong Huo; Yu-Hai Bao; Zhen-Yu Wang; Feng Ling (Neuroscience Bulletin, 2013)

Determination of Concentration of Methotrexate Enantiomers in Intracellular and Extracellular Fluids of HepG2 Cells by Liquid Chromatography–Tandem Mass Spectrometry - Rong Wang; Lifang Guo; Hua Xie; Juanhong Zhang; Xiaoyun Li; Wenbing Li; Jianfeng Wang; Xiaoyu Wu; Zhengping Jia (Cell Biochemistry and Biophysics, 2013)

Effects of Recombinant Human AMH on SCF Expression in Human Granulosa Cells - Rong Hu; Yan Lou; Fei-Miao Wang; Hui-Ming Ma; Xing Wu; Xiao-Mei Zhang; Juan Li; Ying-Pu Sun (Cell Biochemistry and Biophysics, 2013)

Comments on ‘Influences of the Bermuda High and atmospheric moistening on changes in summer rainfall in the Atlanta, Georgia region, USA ’ - Wenhong Li; Laifang Li; Rong Fu; Yi Deng; Hui Wang (International Journal of Climatology, 2013)
In a recent article, Diem (2012) examined the impact of the North Atlantic Subtropical High ( NASH ) and atmospheric moistening on summer rainfall variability in the Atlanta, Georgia region. In his paper, he indicated that the results concerning the variability of the NASH western ridge discussed in Li et al . (2011) are incorrect. We present new evidence here to show that the comments by Diem (2012) are unjustified; the main conclusions in Li et al . (2011) were drawn according to the data over a 60‐year (1948–2007) and 45‐year (1958–2002) periods of NCEP / NCAR and ERA ‐40 reanalysis, whereas conclusions of Diem (2011) were based upon the trend analysis of a similar but different index of the NASH using sub‐periods of 1948–2009 (since late 1970s). The comment emphases the importance of climate dynamics to study precipitation variability over the Southeastern US and further strengthens the conclusions originally put forth in Li et al . (2011): over the last 60 years (1948–2007), the NASH has shown a significant trend of westward movement, and the meridional movement of the NASH western‐ridge (i.e. its latitudinal change) has enhanced in the recent three decades.

A Highly Selective Turn-On Fluorescent Chemosensor for Zinc Ion in Aqueous Media - Zeng-chen Liu; Zheng-yin Yang; Yan-xia Li; Bao-dui Wang; Yong Li; Tian-rong Li; Yong-jie Ding (Journal of Fluorescence, 2013)

Identification and characterization of Pestalotiopsis spp. causing twig blight disease of bayberry (Myrica rubra Sieb. & Zucc) in China - Hai-Ying Ren; Gang Li; Xing-Jiang Qi; Li Fang; Han-Rong Wang; Ji-Guang Wei; Shaobin Zhong (European Journal of Plant Pathology, 2013)

Discovery of a novel esterase subfamily sharing an identified arm sequence (ArmEst) by gene-specific metagenomic PCR - Ao Zhang; Rong Zhao; Peng Jin; Lifang Ma; Xiaolong Xiong; Tian Xie; Xiaolin Pei; Li Yu; Xiaopu Yin; Qiuyan Wang (Biotechnology Letters, 2013)

A chloroplast membrane protein LTO1/AtVKOR involving in redox regulation and ROS homeostasis - Ying Lu; Hua-Rong Wang; Han Li; Hao-Ran Cui; Yue-Guang Feng; Xiao-Yun Wang (Plant Cell Reports, 2013)

Addition of Co2+ to culture medium decides the functional expression of a recombinant nitrile hydratase in Escherichia coli - Xiaolin Pei; Qiuyan Wang; Chenglu Li; Xiaopu Yin; Rong Chen; Tian Xie (Biotechnology Letters, 2013)

Screening of high α-arbutin producing strains and production of α-arbutin by fermentation - Chun-Qiao Liu; Li Deng; Peng Zhang; Shu-Rong Zhang; Luo Liu; Tao Xu; Fang Wang; Tian-Wei Tan (World Journal of Microbiology and Biotechnology, 2013)

Identification of miR-221 and -222 as important regulators in genotype IV swine hepatitis E virus ORF3-expressing HEK 293 cells - Ying Cheng; Li Du; Qiaoyun Shi; Hanwei Jiao; Xiaoru Zhang; Yongchang Hao; Hui Rong; Jianing Zhang; Xiaoxiao Jia; Shiyu Guo; Wenhua Kuang; Hui Zhang; et al. (Virus Genes, 2013)

Engineering geological assessment for route selection of railway line in geologically active area: A case study in China - Run-qiu Huang; Yan-rong Li; Ke Qu; Ke Wang (Journal of Mountain Science, 2013)
The Cheng-Lan railway links Chengdu, a central city in Southwestern China, and Lanzhou, a central city in Northwestern China. The railway passes through the Longmenshan fault zone (Wenchuan earthquake happened there on May 12, 2008), Minjiang fault zone, and Dongkunlun fault zone, which are all active. It runs over the Yangtze River and the Yellow River, and crosses high mountains and deep valleys. There exists, along the railway’s alignment, different kinds of strata of hard granite and soft, weak metamorphic rocks such as carbonaceous slate, schist, and phyllite. It is, therefore, a key issue for such an infrastructure construction to assess the engineering geological conditions and risks, so as to mitigate or avoid possible georisks and to offer optional designs. Geological survey and georisk assessment along the railway corridor are carried out. Special attention is given to active faults, earthquakes and seismic zones. Based on these, discussions about geological aspects for route selection of the railway are conducted and countermeasures for georisk control are proposed accordingly. Main conclusions are achieved as follows: (1) Geohazards such as landslides, rockfalls and debries flows dominate both the route selection of the railway and the engineering structures (e.g., tunnels or bridges) adopted; (2) Tunnel has been proved to be an excellent structure for linear engineering in geologically active area; and (3) In the case where avoiding is impractical, necessary protection measures should be taken to engineering slopes in high earthquake intensity areas, especially the area with earthquake of Ms. 8 or greater.

Halomonas socia sp. nov., isolated from high salt culture of Dunaliella salina - Jiao Cao; Huai-Yuan Ma; Hai-Yu Li; Kui-Rong Wang; Kun Ruan; Lin-Han Bai (Extremophiles, 2013)

Physical characteristics of Chinese Hakka - LianBin Zheng; YongLan Li; ShunHua Lu; JinPing Bao; Yang Wang; XiaoRui Zhang; Hong Xue; WenGuo Rong (Science China Life Sciences, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Exome Sequencing Identified NRG3 as a Novel Susceptible Gene of Hirschsprung’s Disease in a Chinese Population - Jun Yang; Shengyu Duan; Rong Zhong; Jieyun Yin; Jiarui Pu; Juntao Ke; Xuzai Lu; Li Zou; Hongmei Zhang; Zhidong Zhu; Depeng Wang; Huasheng Xiao; et al. (Molecular Neurobiology, 2013)

Prostaglandin E2 receptor EP1 phosphorylate CREB and mediates MMP2 expression in human cholangiocarcinoma cells - Bo Sun; Rong Rong; Hai Jiang; Hai Zhang; YiPin Wang; Xiaoming Bai; Min Zhang; Juan Ma; Shukai Xia; Wei Shu; Li Zhang; Jing Leng (Molecular and Cellular Biochemistry, 2013)

Musca Domestica Larva Lectin Induces Apoptosis in BEL-7402 Cells Through a Ca2+/JNK-mediated Mitochondrial Pathway - Chun-Ling Wang; Yan Xia; Jian-Zeng Nie; Minghui Zhou; Rong-Ping Zhang; Li-Li Niu; Li-Hua Hou; Xiao-Hong Cao (Cell Biochemistry and Biophysics, 2013)

Expression of yeast acyl-CoA-∆9 desaturase leads to accumulation of unusual monounsaturated fatty acids in soybean seeds - Jin-Ai Xue; Xue Mao; Zhi-Rong Yang; Yong-Mei Wu; Xiao-Yun Jia; Li Zhang; Ai-Qin Yue; Ji-Ping Wang; Run-Zhi Li (Biotechnology Letters, 2013)

SIRT1 inhibits TNF-α-induced apoptosis of vascular adventitial fibroblasts partly through the deacetylation of FoxO1 - Weirong Wang; Chunfang Yan; Jiye Zhang; Rong Lin; Qinqin Lin; Lina Yang; Feng Ren; Jianfeng Zhang; Meixi Ji; Yanxiang Li (Apoptosis, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Effects of novel bioorganic fertilizer produced by Bacillus amyloliquefaciens W19 on antagonism of Fusarium wilt of banana - Beibei Wang; Jun Yuan; Jian Zhang; Zongzhuan Shen; Maoxing Zhang; Rong Li; Yunze Ruan; Qirong Shen (Biology and Fertility of Soils, 2013)

Cutaneous and Mucosal Phaeohyphomycosis Caused by Exophiala spinifera in a Pregnant Patient: Case Report and Literature Review - Le Wang; Xiaodong She; Guixia Lv; Yongnian Shen; Qing Cai; Rong Zeng; Caixia Li; Yiping Ge; Shuwen Deng; G. S. de Hoog; Min Li; Weida Liu (Mycopathologia, 2013)

Enhancing production of a 24-membered ring macrolide compound by a marine bacterium using response surface methodology - Hua Chen; Mian-bin Wu; Zheng-jie Chen; Ming-lu Wang; Jian-ping Lin; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Lipopolysaccharide-induced failure of the gut barrier is site-specific and inhibitable by growth hormone - Chao Yue; Wei Wang; Wei-Liang Tian; Qian Huang; Ri-Sheng Zhao; Yun-Zhao Zhao; Qiu-Rong Li; Jie-Shou Li (Inflammation Research, 2013)

Lyssavirus surveillance in bats of southern China’s Guangxi Province - Zhuan-Ling Lu; Wen Wang; Wei-Li Yin; Hai-Bo Tang; Yan Pan; Xiang Liang; Qi Liu; Yi Xiong; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Sloping farmland identification using hierarchical classification in the Xi-He region of China - Yi Li; Jianhua Gong; Dongchuan Wang; Leping An; Rong Li (International Journal of Remote Sensing, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Triterpenoid saponins from the root of Anemone tomentosa - Yi Wang; Wei Kang; Liang-jian Hong; Wen-li Hai; Xiao-yang Wang; Hai-feng Tang; Xiang-rong Tian (Journal of Natural Medicines, 2013)

The Diagnostic Value of Treadmill Exercise Test Parameters for Coronary Artery Disease - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)